2011
DOI: 10.1371/journal.pone.0019077
|View full text |Cite
|
Sign up to set email alerts
|

miR-132 Mediates the Integration of Newborn Neurons into the Adult Dentate Gyrus

Abstract: Neuronal activity enhances the elaboration of newborn neurons as they integrate into the synaptic circuitry of the adult brain. The role microRNAs play in the transduction of neuronal activity into growth and synapse formation is largely unknown. MicroRNAs can influence the expression of hundreds of genes and thus could regulate gene assemblies during processes like activity-dependent integration. Here, we developed viral-based methods for the in vivo detection and manipulation of the activity-dependent microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 51 publications
8
127
0
Order By: Relevance
“…This parallels the time course of expression of WT miR-132, which increases in expression within doublecortinand NeuN-positive cells, but is absent in nestin-positive precursors (Luikart et al 2011). Collectively, these observations suggest that the miR-132/-212 locus is excised by the Cre driver in maturing granule cells in our cKO animals.…”
Section: Discussionsupporting
confidence: 74%
“…This parallels the time course of expression of WT miR-132, which increases in expression within doublecortinand NeuN-positive cells, but is absent in nestin-positive precursors (Luikart et al 2011). Collectively, these observations suggest that the miR-132/-212 locus is excised by the Cre driver in maturing granule cells in our cKO animals.…”
Section: Discussionsupporting
confidence: 74%
“…Because of their seemingly antagonistic actions, we set out to determine whether miR-134 and miR-132 were, in fact, expressed concurrently. Earlier studies indicated that miR-132 was expressed generally throughout the brain, including large pyramidal neurons (17,18,27,29). Because the preponderance of neurons in the cortex are excitatory, we hypothesized that miR-134, at a minimum, would be expressed in this neuronal subtype.…”
Section: Discussionmentioning
confidence: 96%
“…[123][124][125] Mechanistically, miR-132 is rapidly induced by BDNF in order to regulate dendritic morphogenesis by targeting a Rho GTPase protein, p250GAP (Fig. 1).…”
Section: Mir-34amentioning
confidence: 99%